Análise paleográfica de um manuscrito de auto cível de liberdade (1878) - SOUZA, Marilene Andreza Guerreiro de (2023)
This research is constituted through a paleographic analysis of a handwritten document of civil liberty, belonging to the collection of the Public Archive of the State of Pará (APEP). The choice of this theme arose from the author's experiences as an intern at the Institution during the years 2016 and 2017 and also through the discipline of Paleography, taught during the graduation in Archivology. For this, the reading, transcription, identification and analysis of the graphic aspects of the manuscript were carried out. From the methodological perspective, the research had an exploratory character, based on bibliographical and documentary research, which provided an in-depth look at the subject studied, based on the main authors who discuss Paleography and the black presence in the Amazon. In view of the contact with several manuscripts, a document of a freed black woman who asks for her son's freedom was selected for the application of the proposed objectives. As a result of the research, the spelling of the time was identified, taking into account the type of letter, the proper way of writing, the relationship of words with a spelling different from the current one, the accentuation of words, the identification and development of abbreviations, the support , the type of ink and the writing instrument. With regard to the complementary aspects, the relationship between the author and the applicant with the manuscript, date, origin and space was carried out. It concludes by reaffirming the importance of discussing the protagonism of the black presence in the Amazon and Paleography for accessing and understanding the information contained in the documents.